2023
DOI: 10.1111/dom.14958
|View full text |Cite
|
Sign up to set email alerts
|

Association of long‐term hyperglycaemia and insulin resistance with brain atrophy and cognitive decline: A longitudinal cohort study

Abstract: Aim: To investigate the longitudinal changes in brain volume and cognitive function associated with diabetes at midlife, and to examine whether long-term hyperglycaemia, insulin resistance or secretory function is associated with brain atrophy and cognitive decline. Materials and Methods:We used data from 2377 participants with both baseline and 4-year follow-up brain magnetic resonance images and neuropsychological measures from the Ansan cohort of the Korean Genome Epidemiology Study. Timeweighted mean glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Dysfunctional insulin signaling and elevated blood glucose levels lead to heightened expression and activation of NF-κB, a pivotal participant in the inflammatory cascade and a regulator of apoptosis ( Sima et al, 2009 ; Moulton et al, 2015 ). Moreover, advanced glycation end products, also leads to inflammation, as a consequence of chronic activation of microglia, leading to neuronal and glial apoptosis ( Moulton et al, 2015 ; Sun et al, 2020 ; Yu et al, 2023 ). We favour the view that neurodegenerative processes underlying T2DM’s pathophysiology might also leads to the presence of brain atrophy, where toxic glucose levels have a harmful impact on various biochemical processes associated with tau integrity, promoting tau cleavage and phosphorylation ( Kubis-Kubiak et al, 2019 ; Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional insulin signaling and elevated blood glucose levels lead to heightened expression and activation of NF-κB, a pivotal participant in the inflammatory cascade and a regulator of apoptosis ( Sima et al, 2009 ; Moulton et al, 2015 ). Moreover, advanced glycation end products, also leads to inflammation, as a consequence of chronic activation of microglia, leading to neuronal and glial apoptosis ( Moulton et al, 2015 ; Sun et al, 2020 ; Yu et al, 2023 ). We favour the view that neurodegenerative processes underlying T2DM’s pathophysiology might also leads to the presence of brain atrophy, where toxic glucose levels have a harmful impact on various biochemical processes associated with tau integrity, promoting tau cleavage and phosphorylation ( Kubis-Kubiak et al, 2019 ; Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that IR is the main mechanism of brain abnormalities in magnetic resonance imaging (MRI) of patients with or without diabetes. [25,26] Neverthless, Ji Hee Yu, et al [27] examined whether long-term hyperglycemia, insulin resistance, or secretory function is associated with brain atrophy and cognitive decline in subjects from the Ansan cohort of the Korean Genome Epidemiology Study (KoGES) , finding time-weighted HOMA-IR level during a 10-year period did not show an association with brain atrophy, unlike baseline insulin resistance markers. Similarly, a longitudinal study reported that there was no correlation between insulin secretion assessed by insulinogenic index (IGI) obtained through oral glucose tolerance test (OGTT) and cognitive function of participants without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to glucose homeostatic mechanisms, the brain is resilient to minor changes in blood glucose levels, but moderate or severe hypo- or hyperglycaemia can impair neuronal functioning and lead to cell death [ 20 , 21 , 22 ]. Recurrent episodes of hypo- or hyperglycaemic states are associated with increased risk of cognitive impairment and dementia [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%